En face OCT in choroideremia. (2nd November 2019) - Murro, Vittoria; Mucciolo, Dario Pasquale; Sodi, Andrea; Giorgio, Dario; Passerini, Ilaria; Pelo, Elisabetta; Virgili, Gianni; Rizzo, Stanislao
ABSTRACT: Purpose : To describe the outer retinal tubulation (ORT) morphology using En face OCT elaboration in a large group of patients affected by choroideremia (CHM). Material and Methods : We retrospectively reviewed CHM patients examined at the Regional Reference Center for Hereditary Retinal Degenerations at the Eye Clinic in Florence. We took into consideration genetically confirmed CHM patients with ophthalmological, fundus autofluorescence (FAF) and optical coherence tomography (OCT) examinations. Results : We studied en face OCT features of ORTs in 18 CHM patients, for a total of 36 eyes; (average age 33 years; SD 19, 2; range 13–77 years). ORTs were found in 30 eyes of 15 patients (15/18; 83, 3% of the patients). We identified 3 en face OCT patterns: round lesions with scalloped boundaries which involved the peripapillary area with more or less evident pseudodendritic ORTs (PD-ORT) (pattern p; 26, 7%); central islands with PD-ORTs (pattern i; 53, 3%); residual outer retinal areas with no ORTs (pattern r; 20, 0%). Conclusions : In CHM, en face OCT imaging allows us to observe various morphological features of the ORTs in different stages of disease, not detectable with other imaging techniques. ORTs were not identified in the mildest phenotypes. En face OCT is a non-invasive useful tool in the characterization and monitoring of the disease.